2002
DOI: 10.1099/0022-1317-51-10-844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactoferrin feeding on the host antifungal response in guinea-pigs infected or immunised with Trichophyton mentagrophytes

Abstract: Earlier studies revealed that oral administration of lactoferrin (LF), a multi-functional milk protein, facilitated curing of dermatophytosis in guinea-pigs and man by an unknown mechanism. The present study aimed to assess the effect of feeding bovine LF on the host antifungal defence systems in guinea-pigs infected or immunised with Trichophyton mentagrophytes, a dermatophytosis-causing fungus. The unbound ironbinding capacity (UIBC) of the plasma of individual animals varied, and plasma with higher UIBC inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Further examination is necessary of the influence of LF feeding on immunological events in the oral tissue using this model. In the past few years, several immunomodulatory effects of ingested LF in animals have been reported (Sekine et al, 1997;Wakabayashi et al, 2002). Very recently, we showed that LF feeding augmented macrophage activity at the local site where inactivated Candida was injected as a priming agent (Wakabayashi et al, 2003).…”
Section: Kinetics Of Numbers Of Pbl and Cln Cellsmentioning
confidence: 89%
“…Further examination is necessary of the influence of LF feeding on immunological events in the oral tissue using this model. In the past few years, several immunomodulatory effects of ingested LF in animals have been reported (Sekine et al, 1997;Wakabayashi et al, 2002). Very recently, we showed that LF feeding augmented macrophage activity at the local site where inactivated Candida was injected as a priming agent (Wakabayashi et al, 2003).…”
Section: Kinetics Of Numbers Of Pbl and Cln Cellsmentioning
confidence: 89%
“…However, it seems more likely that ingested lactoferrin indirectly promotes systemic immune responses 26,28 , because oral lactoferrin is subject to pepsin proteolysis and may not reach the systemic circulation to a large extent 29 . The host defense against microbial infection may be enhanced by lactoferrin via a network of intestinal mucosal and systemic immunity 14,[29][30][31] . In addition, it has been reported that oral intake of bovine lactoferrin enhanced the production of interleukin-18 in intestinal epithelial cells and of interferon-g in the lamina propria, and increased the numbers of CD4 þ , CD8 þ , and natural killer cells in the intestinal mucosa of both tumor-bearing mice and normal mice 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of macrophage activities was detected by nitric oxide production, inhibition of Candida growth, and IFN-g and IL-12 levels in the peritoneal cavity [54]. In guinea pigs that were immunized with inactivated Trichophyton mentagrophytes, bLf feeding enhanced splenocyte secretion of a humoral factor that promotes fungicidal activity of macrophages [55]. Recently, clinical trials were conducted that explored immuno-modulatory effects of bLf.…”
Section: Suggested Function Of the Si-lfrmentioning
confidence: 98%